2012
DOI: 10.1051/alr/2012034
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of donor effect on cultured pearl quality from a duplicated grafting experiment onPinctada margaritiferausing wild donors

Abstract: -Producing high quality cultured black pearls from Pinctada margaritifera is one of the major challenges for the "pearl oyster" industry in French Polynesia. In order to assess donor effect on cultured pearl quality, wild Pinctada margaritifera originating from the Tuamotu Archipelago were used in a duplicated grafting experiment. After 12 months of culture, nucleus retention was assessed and seven pearl quality traits recorded on the 454 cultured pearls harvested from the experiment. The traits scored were na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 22 publications
10
53
2
Order By: Relevance
“…The main result is that highly significant progeny effects exist for several traits of interest: nucleus retention, nacre thickness, nacre weight, pearl darkness, visually perceived pearl colour (bodycolor and overtone), pearl shape categories, surface defects and lustre, the last two of which are components of the Tahitian classification grade. These results are consistent with those obtained by Tayale et al (2012) where the authors demonstrated in a duplicated experimental graft, that individual wild donors of implanted mantle grafts significantly affect seven of the studied quality trait in P. margaritifera cultured pearls (pearl shape categories were not studied in Tayale et al 2012). In contrast, no significant progeny effect was recorded for oyster mortality or pearl circles.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The main result is that highly significant progeny effects exist for several traits of interest: nucleus retention, nacre thickness, nacre weight, pearl darkness, visually perceived pearl colour (bodycolor and overtone), pearl shape categories, surface defects and lustre, the last two of which are components of the Tahitian classification grade. These results are consistent with those obtained by Tayale et al (2012) where the authors demonstrated in a duplicated experimental graft, that individual wild donors of implanted mantle grafts significantly affect seven of the studied quality trait in P. margaritifera cultured pearls (pearl shape categories were not studied in Tayale et al 2012). In contrast, no significant progeny effect was recorded for oyster mortality or pearl circles.…”
Section: Discussionsupporting
confidence: 90%
“…These data are consistent with those of Tayale et al (2012) on P. margaritifera wild donors, where: 1) extreme nucleus retention rate were comparable with 51% to 77% and 2) wild donors had a significant effect on nucleus retention. Cochennec-Laureau et al (2010) have already suggested that rejection phenomena are linked to a number of causes, among which choice of donor oyster is important.…”
Section: Nucleus Retention and Oyster Mortalitiessupporting
confidence: 89%
See 2 more Smart Citations
“…Shell and cultured pearl formation result from the bio-mineralization activities of two distinct tissues in a grafted pearl oyster: the mantle of the recipient oyster and the pearl sac built from graft tissues from the donor [5]. The pearl weight finally attained depends on several factors, including whether or not the donor oyster originated from the wild [8] or from a hatchery-produced family [9,10]. Some studies have shown phenotypic correlations between pearl weight and recipient oyster shell traits, e.g., for Pinctada fucata [11][12][13].…”
Section: Introductionmentioning
confidence: 99%